Thin-shell wormholes in neo-Newtonian theory - Övgün, Ali; Salako, Ines G. (World Scientific Publ Co Pte Ltd, 2017)
In this paper, we constructed an acoustic thin-shell wormhole (ATW) under neo-Newtonian theory using the Darmois-Israel junction conditions. To determine the stability of the ATW by applying the cut-and-paste method, we found the surface density and surface pressure of the ATW under neo-Newtonian hydrodynamics just after obtaining an analog acoustic neo-Newtonian solution. We focused on the effects of the neo-Newtonian parameters by performing stability analyses using different types of fluids, such as a linear barotropic fluid (LBF), a Chaplygin fluid (CF), a logarithmic fluid (LogF), and a polytropic fluid (PF). We showed that a fluid with negative energy is required at the throat to keep the wormhole stable. The ATW can be stable if suitable values of the neo-Newtonian parameters zeta, A, and B are chosen.
Keywords: Thin-shell wormhole; Darmois-Israel formalism; canonical acoustic black hole; stability; neo-Newtonian theory